An Enhanced GC/MS Procedure for the Identification of Proteins in Paint Microsamples. (1st April 2018) - Fico, D.; Margapoti, E.; Pennetta, A.; De Benedetto, G. E.
Abstract : The chemical characterization of materials used in works of art is extremely useful for gaining a better knowledge of the artistic heritage and to guarantee its preservation. A derivatization GC/MS procedure for the identification of proteins in a microsample from painted works of art has been optimized. The amino acid fraction is derivatized using anhydrous dimethylformamide (DMF) as solvent instead of pyridine (Py), commonly used to facilitate the reaction. Although pyridine is often considered a silylation catalyst, there are many instances in which silylation reactions actually are slower in pyridine than other solvents. In addition, pyridine also may have other undesirable effects such as the promotion of secondary products and other chromatographic anomalies. Using DMF, the formation of artifacts is limited and the derivatization yield of hydrophilic amino acids such as proline and hydroxyproline has improved, thus making the identification of organic paint media more straightforward. The method has been validated and successfully applied to identify the binder of the sample taken from the pictorial cycle of the 12th century monastery of Santa Maria delle Cerrate (Lecce, Italy), thus highlighting the use of eggs as a binding medium.